Facilely tunable core-shell Si@SiOx nanostructures prepared in aqueous solution for lithium ion battery anode. (10th May 2020) - Guo, Jianguang; Zhai, Wei; Sun, Qing; Ai, Qing; Li, Jing; Cheng, Jun; Dai, Linna; Ci, Lijie
Abstract: Silicon with higher theoretical capacity than that of the commercial graphite anode is considered as the next generation lithium ion battery anode materials. Herein, our research demonstrates that the surface SiOx coating with silanol groups generated in aqueous solution on silicon nanoparticles can efficiently improve their electrochemical performance. The SiOx layer can suppress the volume expansion of silicon particles, and the surficial silanol groups can also contribute to the enhanced electrochemical performance. Both coulombic efficiency and cycling stability can be improved with the optimal SiOx coating thickness. This work provides a facile avenue of surface engineering of silicon nanoparticle for the high-performance lithium ion battery Si anode.